Oxford international primary Science: student book 4 - Roberts, Deborah; Hudson, Terry (Karachi : Oxford university press, 2023)
A complete six-year primary Science course that takes a problem-solving approach to teaching young learners the skills they need to think like scientists. Features Enquiry-based approach to primary Science promotes scientific understanding Active learning approach with participation from every student Students learn to work scientifically through engaging experiments and investigations Students develop lifelong skills through learning Science Communication activities help EAL students develop fluency in scientific language ?
Keywords: Science - text book